Alive and kicking: the benefits of scuba diving leisure for older Australian women. Issue 4 (8th August 2019) - Gregory, Sally F.; Dimmock, Kay
ABSTRACT: As the number of older people in the developed world continues to rise, attention has turned to the contribution of leisure activities to quality of life. Leisure behaviour has been studied in numerous activities, including outdoor leisure. Scuba diving research has revealed the typical diver profile to be young and male. Yet with an active and ageing population, these stereotypes are being challenged. One notable group is the over 40s female diver. To understand more about leisure and older women, a qualitative study investigated the benefits scuba diving brings to a group of mature aged Australian women. Utilizing empirical research conducted in a beachside community, this research revealed the benefits older women gained from participation in diving activities and how diving activities contributed to their well-being. Findings contribute to the knowledge of serious leisure and continuation theory for adventurous older Australian women, an unexplored segment of the growing scuba diving community.